An Autopsy Case of Fulminant Systemic Infection of Clostridium perfringens With a Diverse Role of Toxins in a Healthy Patient - Ayano Osamura; Hiromi Onizuka; Kenta Masui; Kumiko Murakami; Tomoko Yamamoto; Yoji Nagashima; Munekazu Takeda; Atsushi Kurata (Hindawi Limited, 2024)
We herein report an autopsy case of a fulminant Clostridium perfringens (C. perfringens or Welch bacilli) infection in a healthy adult. A 72-year-old, immunocompetent man visited the emergency department with lower back pain, and blood test revealed hemolytic attack. His condition rapidly worsened with severe acidosis and anemia, and he died despite symptomatic treatment. An autopsy examination demonstrated an abscess with necrosis and air spaces in the right lobe of his liver. Numerous Gram-positive bacilli were seen in the liver and bone marrow, and C. perfringens was identified in culture of the antemortem blood sample. Of note, a mucosal epithelium of the ileum showed loss of tight junctions (claudin 4), suggesting the involvement of C. perfringens toxins with its systemic spreading. Welch toxins were suggested to be involved in serious pathological conditions such as hemolytic anemia and systemic infections, and it is necessary to raise Welch infection as one of the differential diagnoses for fulminant systemic infections even in healthy individuals.